Knowledge on Intrapartum Danger Sign Influences Place of Delivery: The Case of Raya Kobo District, Northeastern Ethiopia - Yimer, Nigus Bililign; Liben, Misgan Legesse (International Journal of Child Health and Nutrition, 2021)
Background: A skilled birth attendance for every pregnant woman during childbirth is the most crucial intervention for improving maternal health. This study aimed to assess institutional delivery service utilization and associated factors among mothers who gave birth in the last 12 months in Raya Kobo district, Ethiopia. Methods: A community-based cross-sectional study was carried out in the Raya Kobo district of Amhara Regional State during March 2016. Logistic regression analysis was performed to assess the association between each independent variable and the outcome variable. Variables with a p-value <0.05 were considered significant. Results: A total of 493 mothers were included in the study, with a response rate of 95.4%. The mean (+SD) age of the study participants was 29.13 (±6.93) years. About 73% of the study participants had attended at least one antenatal care follow up for their last pregnancy, and 56.6% (95% CI: 52.0, 61.0%) gave birth at health institutions. Travelling for 30 minutes and less [AOR=2.95(1.89, 4.58)], attending antenatal care [AOR=6.0(3.55, 10.13)], having knowledge about intrapartum danger signs [AOR=2.48(1.44, 4.24)] and getting information from health extension workers (HEWs) regarding maternal health services were positively associated. Conclusion: The district health office should strengthen its effort to provide free ambulance accessibility and provide information on danger signs of intrapartum complications and the importance of using institutional delivery service to every mother who came to the antenatal clinic. Furthermore, the district health officials should focus on strengthening the capacity of HEWs in relation to maternal health services.